Pengelolaan Sarana dan Prasarana Pendidikan di SMP Negeri 2 Kepung Tahun Ajaran 2020/2021 - Laili Khusna Kurin; Khoirotul Izzah (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Management of educational facilities and infrastructure is the most important thing to support the teaching and learning process so that it can be carried out effectively and efficiently. In this case, the researcher examines how the procurement, storage and maintenance will be carried out at SMPN 2 Kepung in the 2020/2021 school year. The purpose of this study was to determine how the procurement, storage and maintenance carried out at SMPN 2 Kepung in supporting the teaching and learning process for the 2020/2021 school year. This research is descriptive qualitative research. Sources of information in this study are staff/managers of educational facilities and infrastructure who assist in the management of educational facilities and infrastructure at SMPN 2 Kepung. The data collection technique here uses the method of interviewing, observation and documentation. The results of this study indicate that: (1) The implementation of the provision of educational facilities and infrastructure carried out at SMPN 2 Kepung at this time is adding fewer student worksheets to facilitate the teaching and learning process, making small holes to cope with flooding, beautifying the school garden by planting various flowers, processing organic waste for fertilizers and so on; (2) The storage of facilities at SMPN 2 Kepung is currently good enough in terms of checking, grouping, data collection and separation as well as providing a safe place for existing facilities and infrastructure so that the goods to be stored or stored are tidy and easy to search. as well as a collection when needed; (3) The maintenance carried out at SMPN 2 Kepung involves all school members under the supervision and direction of the school principal so that later it can foster the concern of all school residents for the existing school facilities and infrastructure. In addition, the existence of rules and regulations added by the manager of facilities and infrastructure is used to control the use and borrowing of existing facilities and infrastructure within the school.